Growth of a KDP (KH₂PO₄) twin crystal and comparison of its characteristics with a single crystal - Javidi, S.; Esmaeil Nia, M.; Ali Akbari, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
KDP single and twin (prepared from two-glued seeds) crystals have been
grown by the method of temperature reduction. Then, the grown crystals were cut and
polished in the (100) direction for optical characterization. The transmission spectra and
XRD analysis of the crystals were determined and compared. The Vickers microhardness
tests carried out on the two types showed that duplication of the crystal lattice did not
reduce the hardness of it.